HIV Vaccines and Cure The Path Towards Finding an Effective Cure and Vaccine (Advances in Experimental Medicine and Biology,, 2018)
This book provides a comprehensive review of the major barriers to HIV cure and vaccine. It covers the fundamental virology and immunology leading to HIV transmission, protection from infection and long term HIV persistence on antiretroviral therapy. In addition, strategies being tested to eliminate persistent HIV and the rational design of vaccines to induce protective immunity are covered. This book also discusses the challenges related to the design of clinical trials for testing the safety and efficacy of these innovative approaches. This book will provide a systematic overview and also discuss controversial issues for researchers in virology and immunology, as well as practicing physicians, and scientists in the pharmaceutical industry.